Pharmacoeconomic research of medicines used for allergic rhinitis in children - Nizom Suyunov, Galiya Umurzakhova, Ravil Blatov, Shynar Yegizbayeva, Maksuda Abdullaeva, Kairat Zhakipbekov (Journal of Applied Pharmaceutical Science, 2024)
Allergic rhinitis (AR) is a common global disease, affecting approximately 2%–25% of children and 1%–40% of adults. Recent studies have shown an increasing prevalence, especially in low-income countries. Although not fatal, AR significantly impairs patients’ quality of life and is linked to bronchial asthma (BA) development. This research aimed to study the regional distribution of AR in children, analyze various medicine preparations used for treatment, and identify effective and affordable options through pharmaco-economic methods. Data from the Ministry of Healthcare of the Republic of Uzbekistan, Hospital No. 2 of the Tashkent Medical Academy, and wholesale medicine costs were analyzed. The study demonstrated the effectiveness and cost efficiency of budesonide medicines for treating AR in children with BA, resulting in significant cost savings during the first treatment session.
Keywords: Budesonide, mebhydrolin, chloropyramine, budesonide mometazone furoate, medicines substances